Understanding patterns of pleasure craft tourism in the Canadian Arctic and implications for safety management - De Souza, Elsa (2018)
This study establishes an understanding of pleasure craft tourism patterns in the Canadian Arctic from 1990-2013 with a focus on the implications for safety. Two specific objectives were fulfilled: 1. to develop an understanding of the pleasure craft vessel traffic and pleasure craft travel patterns, and 2. to develop an understanding of incidents, close-calls, and safety issues. Pleasure craft tourism in the Canadian Arctic is a relatively new industry, although it is now the fastest growing marine sector. There is a lack of information on these small vessels compared to larger expedition cruise ships that have been the focus of research and management concerns. The increase in pleasure craft traffic in the region should raise concern about traffic patterns and safety of these tourists because they are traveling in a region with limited infrastructure, services, and search and rescue. Other issues that need examination are behaviour, monitoring, and control of pleasure craft vessels, indicating the need for insight into vessel numbers, spatial patterns, and vessel preparedness. A literature review was conducted to identify the current state of pleasure craft tourism in the Canadian Arctic. This included identifying patterns of vessel traffic, defining pleasure craft and the management context, as well as the management context of Antarctica and the European Arctic. The literature review concludes with the knowledge gaps related to pleasure craft tourism that drive this study. This research takes a quantitative approach to understanding pleasure craft vessels in the Canadian Arctic. This study uses two main sources of data: the Pleasure Craft Dataset, developed specifically for use in this project; and, a database of Internet web logs (Blog File) gathered for this research. The Pleasure Craft Dataset is comprised of information on pleasure crafts extracted from the NORDREG database (for the purposes of this research called the NORDREG pleasure craft data), a publicly available database collected by the Canadian Coast Guard, and data on additional vessels found through a literature review and Internet searches. The first phase of this study involved the analysis of the Pleasure Craft Dataset to explore spatial and temporal patterns. The second phase of this study used content analysis on blogs with material focusing on the experiences of pleasure craft travelers in the Canadian Arctic. The results show an increase in pleasure craft tourism in the Canadian Arctic, and a concentration of vessels and vessels days spent in the Northwest Passage while demonstrating that not all vessels are reporting to NORDREG. Further, vessels days are now greater on a per vessel basis than in the past. The results also indicate an increasing number in pleasure craft travelers overall and the advent of larger pleasure craft vessels to the region. Blog analysis was able to provide insight into pleasure craft travelers and their vessels, including aspects such as: sites visited, behaviour of travelers, and interactions with the environment. The increase in vessel numbers, larger pleasure craft vessels in the region, and the spatial extension of vessel presence presents issues for management in the Canadian Arctic regarding growing pressure on infrastructure, services, and search and rescue. There is a need for further research on pleasure craft tourism in Arctic Canada. Additional research should contribute to this sector of marine tourism by focusing on understanding management implications related to safety, insurance, behaviour controls and monitoring. There is also a need for research into pleasure craft tourism experiences, the views of community members on the sector, and the role of individuals who provide support to pleasure craft tourism formally and informally. There is also a need for policies and guidelines to aid pleasure craft travelers, and quite possibly a need for mandatory pleasure craft reporting to ensure appropriate monitoring and support.